2021
DOI: 10.1002/pssr.202100010
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional CO2 Plasma Treatment at the i/p Interface Enhancing the Performance of Planar Silicon Heterojunction Solar Cells

Abstract: Passivation techniques are regarded as an effective strategy to obtain high-efficiency crystalline silicon (c-Si) solar cells. These include field-effect passivation and chemical passivation. [1] Among high-performance devices, intrinsic hydrogenated amorphous silicon (i-a-Si:H) provides outstanding chemical passivation on the surface of c-Si by saturating the dangling bonds and thus reducing the density of interface. Then, with the addition of thin doped silicon films, transparent conducting oxides (TCOs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Generally, it is quite reasonable to expect that RF nc‐SiO x :H film with high E g would lead to a higher transparency, and hence a higher J sc . However, it has also been reported that RF nc‐SiO x :H films result in a higher series resistance and deteriorated surface passivation, causing both FF and J sc loss 3,12,16,63 . Therefore, it is necessary to explore the different contributions of RF and VHF nc‐SiO x :H films on SHJ solar cell performance more closely.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, it is quite reasonable to expect that RF nc‐SiO x :H film with high E g would lead to a higher transparency, and hence a higher J sc . However, it has also been reported that RF nc‐SiO x :H films result in a higher series resistance and deteriorated surface passivation, causing both FF and J sc loss 3,12,16,63 . Therefore, it is necessary to explore the different contributions of RF and VHF nc‐SiO x :H films on SHJ solar cell performance more closely.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, SHJ solar cells comprise a crystalline silicon (c‐Si) absorber sandwiched by intrinsic and doped hydrogenated amorphous silicon (a‐Si:H) thin layers, transparent conductive oxide (TCO) layers, and screen‐printed metallic finger grid contacts. All the a‐Si:H layers are usually grown by plasma‐enhanced chemical vapor deposition (PECVD), in which the intrinsic hydrogenated amorphous silicon (a‐Si:H(i)) layers passivate the surface of c‐Si by saturating the dangling bonds and thus reducing the density of surface states 3 . The boron‐doped p‐type hydrogenated amorphous silicon (a‐Si:H(p)) and phosphorous‐doped n‐type amorphous silicon (a‐Si:H(n)) layers create back‐surface field (BSF) and front‐surface field (FSF) playing a role of charge carrier selective collection 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another effective method for reducing the incubation layer thickness is the CO 2 plasma treatment. The atomic oxygen can penetrate into the i-a-Si:H, forming highly stressed Si-O-Si bonds on the surface of the film, which facilitates the aggregation of Si clusters and the formation of nanocrystalline phases [22,23]. The CO 2 plasma treatment proves more effective than the seed layer in improving the crystallinity of p-nc-Si:H, but the material σ dark is ~0.2 S cm −1 , which does not meet the needs of carrier transport in high efficiency SHJ solar cells.…”
Section: Effect Of Interface Treatment On the Properties Of P-nc-si:h...mentioning
confidence: 99%